Implementasi Islamic Wealth Management Dalam Mengembangkan UMKM (Studi Kasus Seblak Prasmanan Manggung Gajah Mojokerto) - Nurmaulida, Regita Okti; Mustofa, Mustofa (Jurnal Ilmiah Ekonomi Islam, 2023)
MSMEs are one of the drivers of the economy in Indonesia. In its implementation, there are still many factors that cause MSMEs to still be able to develop as expected. Among them are constraints regarding the knowledge possessed by business managers, as well as related to their ability to manage their finances or business income. This research uses qualitative methods by combining field research and literature research. This study aims to examine the importance of managing wealth in MSMEs from a sharia perspective and to examine how Seblak Buffet Manggung Gajah Mojokerto implements Islamic Wealth Management in its business. The results of the research are in accordance with the stages in Islamic Wealth Management applied to MSMEs Seblak Buffet Manggung Gajah starting from the acquisition or creation of wealth, increasing wealth, protecting wealth, refining wealth and distributing wealth.